2011
DOI: 10.1063/1.3580773
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence dynamics in Ga(AsBi)

Abstract: The temporal evolution of the spectrally resolved luminescence is measured for a Ga(AsBi) sample at low temperatures. The results are analyzed with the help of kinetic Monte Carlo simulations incorporating two disorder scales attributed to alloy disorder and Bi- clustering. An average time of 5 ps is identified as the upper limit for carrier capture into the Bi clusters whereas the extracted hopping rate associated with alloy fluctuations is much faster than the transitions between the individual cluster sites

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
16
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 19 publications
3
16
0
Order By: Relevance
“…27,28 Photoluminescence (PL) experiments have shown that in GaAsBi the radiative recombination occurs on a nanosecond time scale (~ 50 -80 ns). 29,30 Since the laser pulse repeats every 12 ns, the radiative recombination process is not probed in our measurements and the observed lifetime corresponds to the faster recombination via defects. The intermediate decay process (A 2 , ) has a negative amplitude and we will discuss the origin of this process in the rest of this paper.…”
Section: A the Three Processesmentioning
confidence: 99%
“…27,28 Photoluminescence (PL) experiments have shown that in GaAsBi the radiative recombination occurs on a nanosecond time scale (~ 50 -80 ns). 29,30 Since the laser pulse repeats every 12 ns, the radiative recombination process is not probed in our measurements and the observed lifetime corresponds to the faster recombination via defects. The intermediate decay process (A 2 , ) has a negative amplitude and we will discuss the origin of this process in the rest of this paper.…”
Section: A the Three Processesmentioning
confidence: 99%
“…On the other hand, both spatial and valence band tail disorder from Bi incorporation had to be invoked to interpret photoluminescence (PL) experiments. The latter gave a broad low-temperature line width and a non-monotonous temperature dependence of both the PL peak position and the PL line width [27][28][29][30][31] , and had to be explained by two-scale disorder models.…”
Section: Introductionmentioning
confidence: 99%
“…Such a broadening effect is related to the non-uniform distribution of Bi and/or Bi clusters in the GaAsBi layer [27,28]. QW, which becomes strong.…”
Section: Resultsmentioning
confidence: 99%